PEMANFAATAN PANGAN LOKAL MENJADI SNACK SEBAGAI MAKANAN TAMBAHAN BAGI IBU HAMIL - Siti Nur Rochimiwati,; Mas'ud, Hikmawati; Adam, Adriyani (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2022)
Nutritional problems in pregnant women, such as chronic energy deficiency (KEK), are still high. The results of Riskesdas in 2018 for pregnant women in KEK was 14,5%. This situation is caused by insufficient food intake for a long time and infectious diseases. Snacks as supplementary food can increase nutritional information for the short term. The snack can be made from a variety of local foods, which are relatively affordable and can be made by the family. The community service was conducted two days on 14-15 of July 2020 with 30 pregnant women. The activity was done during the pandemic, so we still paid attention to health protocols by delivery of material directly with relatively short time duration, showing a practical video of making snacks which was the original recording of the servants in making snacks and continued with independent practice at the homes of each pregnant woman. The results of this activity indicate the presence of 100% for pregnant women, knowledge of pregnant women based on a questionnaire with the highest score was 84%, the achievement of skills is evaluated from the response (sending picture) of the results of independent practice at home as much as 51.9%. It is hoped that the same activity will be carried out in other groups of pregnant women to improve the nutritional status of pregnant women. --- Masalah gizi pada ibu hamil seperti kurang energi kronis (KEK) masih tinggi. Hasil riskesdas tahun 2018 ibu hamil KEK 14,5%. Keadaan ini disebabkan asupan makanan yang kurang yang berlangsung lama serta adanya penyakit infeksi penyerta. Penanggulangan jangka pendek dengan meningkatkan asupan gizi melalui pemberian snack sebagai makanan tambahan pada ibu hamil. Snack ini dapat dibuat dari berbagai pangan lokal dengan harga relative terjangkau dan dapat dibuat sendiri oleh keluarga. Kegiatan ini dilaksanakan selama 2 hari pada tanggal 14 dan 15 juli 2020 dengan peserta 30 orang ibu hamil. Kegiatan ini dilaksanakan pada masa pandemi sehingga tetap memperhatikan protokol kesehatan sehingga penyampaian materi secara langsung dengan durasi waktu relative singkat, menayangkan video praktek pembuatan snack yang merupakan rekaman asli para pengabdi dalam membuat snack dan dilanjutkan dengan praktek mandiri dirumah masing-masing ibu hamil. Hasil kegiatan ini menunjukkan kehadiran 100% bagi ibu hamil, Pengetahuan ibu hamil berdasarkan kuesioner dengan skor terbanyak yaitu 84%, capaian keterampilan dievaluasi dari respon (pengiriman foto) hasil praktek mandiri dirumah sebanyak 51,9%. Diharapkan kegiatan yang sama dilaksanakan pada kelompok ibu hamil yang lain sehingga dapat meningkatkan status gizi ibu hamil.